2016
DOI: 10.1086/684014
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Savings for Agriculture: Field Experimental Evidence from Malawi

Abstract: We implemented a randomized intervention among Malawian farmers aimed at facilitating formal savings for agricultural inputs. Treated farmers were offered the opportunity to have their cash crop harvest proceeds deposited directly into new bank accounts in their own names, while farmers in the control group were paid harvest proceeds in cash (the status quo). The treatment led to higher savings in the months immediately prior to the next agricultural planting season, and raised agricultural input usage in that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(144 citation statements)
references
References 29 publications
6
137
0
1
Order By: Relevance
“…On the other hand, liquidity might be an obstacle for accumulating savings. While few randomized experiments have shown that commitment savings products help current or former bank clients and cash crop farmers to save for a specific purpose, exercising their self-control early on (Ashraf et al, 2006b;Brune et al, 2014), this study shows that poor households are able to save even with savings accounts without explicit commitments.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…On the other hand, liquidity might be an obstacle for accumulating savings. While few randomized experiments have shown that commitment savings products help current or former bank clients and cash crop farmers to save for a specific purpose, exercising their self-control early on (Ashraf et al, 2006b;Brune et al, 2014), this study shows that poor households are able to save even with savings accounts without explicit commitments.…”
Section: Introductionmentioning
confidence: 59%
“…); whether the account charges opening fees and/or minimum balance fees; whether there are withdrawal fees; whether there are deposit fees; the nominal interest rate and inflation rate; the take-up rate; and the usage rate. 34 Five studies offered an ordinary savings account (Ashraf et al, 2006a;Cole et al, 2011;Dupas and Robinson, 2013a;Dupas et al, forthcoming;Schaner, 2013), one study offered an ordinary savings account with text message reminders (McConnell, 2012), two studies offered ordinary and commitment savings accounts (Brune et al, 2014;Kast and Pomeranz, 2013), and four studies offered commitment accounts (Ashraf et al, 2006b;Karlan and Linden, 2014;Karlan and Zinman, 2013;Karlan et al, 2012).…”
Section: Results: Take-up and Usagementioning
confidence: 99%
See 2 more Smart Citations
“…Our key empirical resultthat, for a high proportion of microfinance clients, credit and savings can act as substitutesis useful for understanding recent research on microfinance. Growing empirical evidence suggests that savings products can be valuable for generating income and for reducing poverty (Burgess and Pande, 2005;Dupas and Robinson, 2013;Brune et al, 2016). Standard microcredit productswith high interest rates and immediate repaymentsincreasingly seem unable to generate enterprise growth (Karlan and Zinman, 2011;Banerjee et al, 2015).…”
Section: Recent Research On Microfinancementioning
confidence: 99%